HUBUNGAN BEBAN KERJA MENTAL DAN STRES KERJA PADA TENAGA KEPENDIDIKAN DI KOTA BATAM - Sri Zetli (Universitas Putera Batam, 2019)
Educators are qualified teaching staff as teachers, lecturers, counselors, tutors, widyaiswara, tutors, instructors, facilitators and other designations that are in accordance with their specialty, and participate in the implementation of education. In accordance with Law No. 14 of 2005 concerning Teachers and Lecturers, professional staff. With different duties and responsibilities between elementary, junior high, high school and lecturers, the workload and work stress that are felt may be different too. NASA - Task Load Index is a method of measuring mental workload subjectively while OHSAS 2010 questionnaire for measuring work stress levels. Data analysis used a correlate person test and ANOVA One Way difference test. From the correlate person test shows the strong correlation between workload and work stress with the correlation of 0.642> r (0.5) between Educators in Batam City. From the ANOVA test, there was a significant difference in mental workload between Educators in the City of Batam with the Sig. is 0.000 <α (0.05). Where the average mental workload for elementary school teachers is 76.98 including the category of heavy mental workload, for junior high school teachers is 67.99 including the category of moderate mental workload, for high school teachers is 66.89 including the category of moderate mental workload and for lecturers is 80.22 including the category of burden heavy mental work. For different tests of work stress, there was a significant difference between Educator Workers in Batam City where Sig. is 0.000 < α (0.05). The average work stress in elementary school teachers is 129.63 (74.08%) in the high category, for junior high school teachers is 104.17 (59.52%) included in the category of moderate work stress, for high school teachers is 109.40 (62.51%) included in the category of moderate work stress and for lecturers is 131.33 (75.05%) included in the category of high work stress.